PENGARUH FITUR VIRTUAL ACCOUNT BILLING, PAYMENT TRANSACTION, DAN E-STATEMENT TERHADAP PENGAPLIKASIAN M-BANKING - Alwan Azhari; Tuti Anggraini (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
Customers experience many problems in making direct transactions through ATM outlets such as waiting for queues at banks, remote home locations, checking bank statements and several other problems. The research aims to see the effect of virtual account billing, payment transactions, and e-statements on customer convenience in applying m-banking. This study used quantitative research methods and distributed questionnaires to 100 respondents of Sharia Banking study program students of North Sumatra State Islamic University 2019 and then processed on the SPSS application Version 29.0. This study shows that simultaneously all variables used, namely virtual account billing, payment transactions, and e-statements simultaneously have a significant influence shown by the results of the F value of the table of 20.782 > 2.70. Partially, payment transaction variables and e-statements have a significant effect on customer convenience. While the virtual account variable has no influence on the ease of customers in applying m-banking.